THE GMP CONCEPT ON THE PRODUCTION OF EEL CHIPS IN "XYZ" SMALL MEDIUM ENTERPRISE, KARANGLO, POLANHARJO, KLATEN - Rahmania Nur Afiah; Niken Kundari; Rizky Brisha Nuary; Lativa Lisya Maghfira (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2023)
Eel chips have a dry, crunchy texture and long shelf life, making them easy to consume as a healthy snack. This study aimed to determine and evaluate the application of the GMP concept in the production process of eel chips in the “XYZ” SME and to recommend the appropriate GMP concept for this SME. The results showed that the eel chips had moisture, FFA, protein, and TPC values of 1.787%, 0.367%, 25.509%, and 2.2x103 colonies, respectively. In addition, the sensory test showed that the eel chips were favourable to the panelists. It can be concluded that the analysis complied with the National Standards. Based on the observations, it was found that there was 1 element for the minor level, 2 elements for the major level, and respectively 7 and 4 elements for serious and critical levels. The result showed that the SME was on level 4, meaning that it is recommended that they had to perform daily internal audits.